Behavior Intention to Stay in a Hotel: Insights Gained from COVID-19 Pandemic in Indonesia: Behavioral Intention - Suzano, Ricky; Jayadi, Handi; Empi, Febi Raharja; wijaya, Lianna (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
The study aims to investigate and examine the determinants impacting tourists' decisions to choose hotel accommodation amidst the COVID-19 outbreak. This investigation adopts a quantitative methodology and employs a descriptive strategy by conducting an online survey targeting tourists residing in the JABODETABEK region. A total of 263 respondents participated in the data collection process, which was subsequently analyzed utilizing the Structural Equation Modeling approach implemented through SMART PLS 3.0. The findings of this research reveal that Perceived Threat exerts a negative impact on the intention to stay at hotels. Conversely, Government and Social Trust exhibit a positive and highly significant effect on the intention to stay. In contrast, Customer Individual Response Efficacy and Hotel Response Efficacy do not affect the intention to stay. Notably, Perceived Threat does not influence Government and Social Trust, as well as Hotel Response Efficacy. Nevertheless, Customer Individual Response Efficacy demonstrates a positive and notably significant influence on both Government and Social Trust, along with Hotel Response Efficacy. This research can provide valuable insights for hoteliers in shaping their strategies and ensuring the long-term success of their businesses in a post-pandemic world.